SPECIFIC FEATURES OF GENETIC PREDISPOSITION TO ASTHMA - I. I. Cherkashina; A. V. Razvodovskaya; S. Yu. Nikulina; V. N. Maksimov; A. B. Averianov (Туберкулез и болезни лёгких, 2016)
Goal of the study: evaluation of the impact of single nucleotide polymorphism (SNP) of rs4129267 gene of interleukin 6 receptor, (IL6R), rs1051730 gene of nicotine receptor 3 (CHRNA3) in the formation of predisposition to asthma among citizens of Krasnoyarsk.Materials and methods. Group of asthma patients included 100 persons while control group included 290 persons. The control group included population sample of relatively healthy people without broncho-pulmonary disorders, residing in Novosibirsk and examined within framework of the international projects of MONICA (Multinational MONItoring of trends and determinants in СArdiovascular disease) and HAPIEE (Health, Alcohol and Psychosocial factors In Eastern Europe).Results of the study. The association was detected between non-allergic asthma and SNP rs4129267 of gene IL6R. The association of asthma with rs1051730 of gene CHRNA3 has not been confirmed.